ผลของกาวพอลิยูริเทนต่อสมบัติการยึดติดระหว่างยางวัลคาไนซ์และหนังสังเคราะห์ (THE EFFECT OF POLYURETHANE ADHESIVE FOR ADHESION PROPERTY OF VULCANIZED RUBBER AND SYNTHETIC LEATHER) - โบว์พัฒนากุล, ตะวัน; ภัทรไพบูลย์ชัย, อรสา (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2010)
งานวิจัยนี้ได้ทำการเตรียมกาวพอลิยูริเทนจากยางธรรมชาติอิพอกไซด์เหลวออกซิไดซ์ (OLENR) โดยแปรสัดส่วนโมลระหว่างยาง OLENR กับไดไอโซไซยาเนต ชนิด 4,4¢ เมธิลลีนบีส (ฟีนิลไอโซไซยาเนต, pMDI) ที่สัดส่วนต่างๆ ซึ่งจากการศึกษาสมบัติการยึดติดระหว่างยางวัลคาไนซ์กับหนังสังเคราะห์ชนิด PVC ตลอดทั้ง PU โดยการทดสอบแบบปอก (peel test) ด้วยมุม 180 องศา พบว่าการใช้กาวพอลิยูริเทนที่สัดส่วนโมลระหว่างยาง OLENR กับไดไอโซไซยาเนตเท่ากับ 1.50 : 1.0 ร่วมกับการปรับผิวหน้ายางวัลคาไนซ์จะให้สมบัติการยึดติดดีที่สุด โดยเฉพาะอย่างยิ่งกับหนังสังเคราะห์ชนิด PVC และให้การยึดติดกับหนังชนิด PU ที่สูงกว่ากาวพอลิยูริเทนทางการค้า สำหรับผลของการปรับผิวหน้ายางวัลคาไนซ์ด้วยสารละลายกรดไตรคลอโรไอโซไซยานูลิกในเอธิลอะซิเตตจะให้ค่าความแข็งแรงในการยึดติดที่ใกล้เคียงกับสารรองพื้นทางการค้า (Dongsung primer) ที่ความเข้มข้นเดียวกัน คำสำคัญ: oxidized liquid epoxidized natural rubber, peel strength, synthetic leather, surface treatment Polyurethane adhesive was prepared from the reaction between the oxidized liquid epoxidized natural rubber (OLENR) with polymeric 4,4'-methylenediphenyl diisocyanate (pMDI) at various mole ratio of NCO/OH. The adhesion between vulcanized rubber and synthetic leathers including of PVC and PU was measured by mean of 180° peel test. The result shown that polyurethane adhesive at 1.5 : 1.0 mol/mol in the presence of surface treatment has excellence peel strength especially with PVC synthetic leathers. This synthesized adhesive also provided higher peel strength in PU synthetic leather than commercial polyurethane adhesive. Moreover, peel strength of vulcanized rubber treated surface with trichloroisocyanuric acid in ethyl acetate was closely to commercial primer, Dongsung at the same concentration. Keywords: oxidized liquid epoxidized natural rubber, peel strength, synthetic leather, surface treatment